1991
DOI: 10.1093/jnci/83.17.1226
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Canine Malignant Lymphoma: Positive Association With Dog Owner's Use of 2, 4-Dichlorophenoxyacetic Acid Herbicides

Abstract: A hospital-based case-control study of companion dogs examined the risk of developing canine malignant lymphoma associated with the use of chemicals in and about the home. Information from a self-administered owner questionnaire and/or a telephone interview of about 491 cases, 466 nontumor controls, and 479 tumor controls indicated that owners in households with dogs that developed malignant lymphoma applied 2,4-dichlorophenoxyacetic acid (2,4-D) herbicides to their lawn and/or employed commercial lawn care co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0
8

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 0 publications
0
84
0
8
Order By: Relevance
“…Chemical carcinogens as a cause of malignant lymphoma In a recent case-control study of canine malignant lymphoma, a small but significant positive association [odds ratio = 1.3] was found with the dog owner's use of 2,4-dichlorophenoxyacetic acid herbicides (37). The results of this study, however, were criticized and found unproven in a report by an expert panel (38).…”
Section: Descriptive Epidemiologymentioning
confidence: 63%
“…Chemical carcinogens as a cause of malignant lymphoma In a recent case-control study of canine malignant lymphoma, a small but significant positive association [odds ratio = 1.3] was found with the dog owner's use of 2,4-dichlorophenoxyacetic acid herbicides (37). The results of this study, however, were criticized and found unproven in a report by an expert panel (38).…”
Section: Descriptive Epidemiologymentioning
confidence: 63%
“…Lawn pesticide use is increasing 5-8% per year in the US and applications are thought to be completed five times more frequently than the application rate that is used on farms (Pimental et al, 1993). Insecticides have also been linked to NHL (Hayes et al, 1991). Additional studies of specific occupations and specific chemicals have suggested some increase in the risk of NHL among exposed persons; however, exposure assessment is quite difficult due to changing patterns over time.…”
Section: Chemical/agricultural Exposuresmentioning
confidence: 99%
“…Seminomas have been reported in military working dogs exposed to herbicides in Vietnam (8). More recently, a positive correlation was found between the incidence of malignant lymphomas in dogs and their owners' use of phenoxyacetic acid herbicides on their lawns (9). Furthermore, an EPA survey of cancer mortality rates in the United States indicated that the mortality rate due to ovarian and other reproductive organ cancers in human females from Washington County, Maine, and near Indian River was significantly higher than the national average (10).…”
Section: Introductionmentioning
confidence: 99%